2011
DOI: 10.1007/s10346-011-0255-y
|View full text |Cite
|
Sign up to set email alerts
|

Report on a recent deep-seated landslide at Gírová Mt., Czech Republic, triggered by a heavy rainfall: The Gírová Mt., Outer West Carpathians; Czech Republic

Abstract: Report on a recent deep-seated landslide at Gírová Mt., Czech Republic, triggered by a heavy rainfall: The Gírová Mt., Outer West Carpathians; Czech Republic Abstract A large deep-seated landslide, triggered by a heavy rainfall, activated early in the morning on May 19, 2010 along the SW slope of Gírová Mt., NE Czech Republic. The landslide occurred within a zone of pre-existing deep-seated gravitational deformation, and it was accompanied with pronounced ground liquefying in the central and lower portion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Recent field investigations in the Flysch Belt of the Outer Western Carpathians led to the discovery of several large rotational-translational slope failures that transformed into shallow earthflows at their frontal parts due to liquefaction of the substrate. These shallow landslides and earthflows are usually much faster and more destructive than their deep-seated precursors (Baroň et al, 2004(Baroň et al, , 2011Klimeš et al, 2009). Here, we propose a new term for this type of slope failurecomplex flow-like landslides (CFLLs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent field investigations in the Flysch Belt of the Outer Western Carpathians led to the discovery of several large rotational-translational slope failures that transformed into shallow earthflows at their frontal parts due to liquefaction of the substrate. These shallow landslides and earthflows are usually much faster and more destructive than their deep-seated precursors (Baroň et al, 2004(Baroň et al, , 2011Klimeš et al, 2009). Here, we propose a new term for this type of slope failurecomplex flow-like landslides (CFLLs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Hsiaolin landslide, after sweeping through the village in its course, formed a short-lived blockage dam, and the continuous inflow triggered follow-up dambreak debris flows (Dong et al, 2011;Li et al, 2011;Tsou et al, 2011). Similar rainfall triggered large scale deep-seated landslide examples and related research include those reported by Cardinali et al (2002), Roering et al (2005), Baroň et al (2011), Chigira (2011), Xu et al (2015), Vallet et al (2015), and Lee et al (2018).…”
Section: Introductionmentioning
confidence: 85%
“…Baroň et al, 2011Baroň et al, : in 2010, in the Czech Carpathians colluvia were transported 253 m downslope during only a few hours - Fig. 1a) compared with slow-moving landslides, where the rate of movement may be less than a centimetre per year (Noferini et al, 2007;Massey et al, 2013).…”
Section: Introductionmentioning
confidence: 96%